2017
DOI: 10.1007/s11248-017-0054-x
|View full text |Cite
|
Sign up to set email alerts
|

Co-precipitation molecules hemopexin and transferrin may be key molecules for fibrillogenesis in TTR V30M amyloidogenesis

Abstract: The disease model of familial amyloidotic polyneuropathy—7.2-hMet30 mice—manifests amyloid deposition that consists of a human amyloidogenic mutant transthyretin (TTR) (TTR V30M). Our previous study found amyloid deposits in 14 of 27 7.2-hMet30 mice at 21–24 months of age. In addition, non-fibrillar TTR deposits were found in amyloid-negative 7.2hMet30 mice. These results suggested that TTR amyloidogenesis required not only mutant TTR but also an additional factor (or factors) as an etiologic molecule. To dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…392-510, including the zinc finger region), which was obtained from PDB (PDB 6B0O chain A). The transferable intermolecular potential with three points (TIP3P) water model 13 and the AMBER03 force field were used for structural optimization of 500-ps molecular dynamics using GROMACS software 14 , as in our previous study 15 . Then, these partial structures were input into APBS software for analysis of the electrostatic surface potential of the DNA binding region, as described previously 16 .…”
Section: Structural Analysis In Silicomentioning
confidence: 99%
“…392-510, including the zinc finger region), which was obtained from PDB (PDB 6B0O chain A). The transferable intermolecular potential with three points (TIP3P) water model 13 and the AMBER03 force field were used for structural optimization of 500-ps molecular dynamics using GROMACS software 14 , as in our previous study 15 . Then, these partial structures were input into APBS software for analysis of the electrostatic surface potential of the DNA binding region, as described previously 16 .…”
Section: Structural Analysis In Silicomentioning
confidence: 99%
“…So, our experimental strategy can achieve high accuracy because we used imitated molecular simulation method for the behavior of biomolecule. In addition, our previous research [29][30][31][32][33][34] suggest the usefulness of this prediction by using our molecular simulation methods.…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, our experimental strategy achieved high accuracy because we used a molecular simulation method which possibly imitates the behavior of the biomolecules. In addition, our previous research [29][30][31][32][33][34] suggested the value of this prediction that utilized our molecular simulation methods. Additional analyses of binding affinities of other spike proteins of SARS-CoV-2 variants with ACE2 may provide greater accuracy, and such experiments are now in progress.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent work demonstrated the ability of TF to physically interact with and prevent the self-assembly and toxicity of b-amyloid peptide oligomers, the amyloidogenic protein species in AD (Giunta et al, 2004;Raditsis et al, 2013). At the same time, recent in vivo data have demonstrated physical interactions between TF and TTR amyloid fibrils (Ohta et al, 2018). Through the use of congophilic fibril formation assays, we demonstrated that iron-free TF at physiologically relevant levels decreased in vitro TTR L55P fibril formation by approximately 60%, implicating TF as a chaperone for hepatic TTRs.…”
Section: Discussionmentioning
confidence: 99%